2020
DOI: 10.1590/0034-761220200262x
|View full text |Cite
|
Sign up to set email alerts
|

Better safe than sorry: leadership sensemaking in the time of COVID-19

Abstract: Government leaders who want to promote a collective response to disrupting events, such as the COVID-19 pandemic, need to foster a shared understanding of the crisis through effective communication. However, the tone and content of communication varies across and within countries and led to conflicting results in terms of collective sensemaking. To understand how government leaders’ messages shape emotional and cognitive responses of citizens, we designed a 2x2 vignette experiment in which we manipulate the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Clements (2020), meanwhile, shows that Democrat-leaning Americans are more likely to follow science-based recommendations for preventative behaviors than their Republican counterparts. Studies outside the US complement these conclusions (Aruguete and Calvo, 2020;Dryhurst et al, 2020;Pickup et al, 2020;Sobral et al, 2020;Calvo and Ventura, 2021;Aruguete et al, 2021).…”
Section: Partisanship and Attitudes Toward Covid-19 Riskmentioning
confidence: 69%
See 2 more Smart Citations
“…Clements (2020), meanwhile, shows that Democrat-leaning Americans are more likely to follow science-based recommendations for preventative behaviors than their Republican counterparts. Studies outside the US complement these conclusions (Aruguete and Calvo, 2020;Dryhurst et al, 2020;Pickup et al, 2020;Sobral et al, 2020;Calvo and Ventura, 2021;Aruguete et al, 2021).…”
Section: Partisanship and Attitudes Toward Covid-19 Riskmentioning
confidence: 69%
“…Green et al (2020) show that US Republican leaders sent very different messages as regards COVID-19 than Democratic leaders while Gollwitzer et al (2020) find that consuming the Republican-leaning Fox News media decreases adherence to preventive measures. Outside the US, scholars have analyzed how variation in framing and messaging by political leaders shapes attitudes toward the pandemic in Brazil (Sobral et al, 2020;Calvo and Ventura, 2021), Mexico (Aruguete et al, 2021), and Argentina (Aruguete and Calvo, 2020). We do not test for elite messaging in our study.…”
Section: Partisanship and Attitudes Toward Covid-19 Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing COVID-19 crisis has highlighted the critical role that leaders play in dealing with unexpected and threatening events (Bundy, Pfarrer, Short, & Coombs, 2017;. Research has already shown that leaders are particularly effective in shaping the meaning of the events and the understanding of evolving crises (Sobral, Carvalho, Lagowska, Furtado, & Grobman, 2020). The present study adds to this literature by examining the role of LMX on alleviating physicians' burnout through its influence on perceived psychosocial job demands and resources, in the extreme context of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 87%
“…Crises management scholarship already highlights the key role of political leadership (Boin & t'Hart, 2003;Boin, t'Hart, McConnell & Preston, 2010;Kapucu, 2006) and our previous special issue also presented evidence about leadership sense-making in time of COVID-19 (see Sobral, Carvalho, Łagowska, Furtado & Grobman, 2020).…”
Section: Key Actors Involved In the Pandemic Responsementioning
confidence: 93%